Sakrament pojednania i pokuty w przygotowaniu nupturientów do zawarcia małżeństwa sakramentalnego - Żarkowski, Andrzej (Ius Matrimoniale, 2019)
The sacrament of penance and reconciliation constitutes an integral part of the Christian life. It restores the state of sanctifying grace lost by man as a result of mortal sin. Confession also plays a major role in the preparation of prospective spouses for being joined in the sacrament of matrimony. No mandatory duty is imposed at this point by the legislation yet the sacrament of penance is strongly recommended before the holy matrimony takes place in order to render it more fruitful. The priest preparing the prospective spouses for the holy matrimony is obliged to raise the question of premarital confession and be of help should the need arise. The confessor of the prospective spouses should be characterised by appropriate spiritual and intellectual formation. He should demonstrate particular tactfulness and thoughtfulness when asking questions, especially those concerning premarital sex. The minister’s teaching ought to result in providing positive guidelines for the future married life. The prospective spouses are supposed to fulfill all the acts of the penitent: repentance, disclosure of sins and reparation. A careful examination of conscience is yet another significant component paving the way for a good confession and fruitful matrimony.